Productive, Distributive, Dynamic, and Allocative Efficiency Improvement Model in Colombian Public Universities: Modelo de mejoramiento de la eficiencia Productiva, distributiva, de asignación y dinámica en las universidades públicas de Colombia - Arenas-Valencia, Wilson; Cabello-Eras, Juan José (Scientia et Technica, 2021)
The measurement of efficiency in public universities has been a topic of interest for researchers and state officials in Colombia; this article presents a model that transcends the view of productive efficiency, and expands it by including aspects of equity with distributive efficiency, of acceptance by society in the allocative efficiency, and finally with the dynamic efficiency includes the time variable, with which the state can measure the stability of the indicators of interest. For the design of the model, multivariate statistical techniques and non-parametric techniques were used, such as Structural Equation Models, Principal Component Analysis, Data Envelopment Analysis, and the Balanced Scorecard. Different ranks are obtained with which university improvement plans were identified, emphasizing public institutions with high quality accreditation. A Balanced Scorecard is proposed with the indicators extracted from the sector databases that met the conditions of the techniques used. This technique suggests a causal relationship between the indicators of distributive, productive, and allocative efficiencies, where the perspective of inclusion forms the basis of the scorecard, affecting the perspective of education and research and the latter influencing the perspective of impact. Finally, it is concluded that the public university sector has great challenges in terms of inclusion and measurement of the satisfaction of society, as well as showing improvement trends in the measured aspects as reflected in the DEA Malmquist index. As a result, a model is obtained for university administrators to identify the aspects in which they must invest the public budget that guarantees the greater multidimensional efficiency of Colombian public universities.